2021
DOI: 10.1002/adts.202100070
|View full text |Cite
|
Sign up to set email alerts
|

Study on Influencing Factors of Consistency in Manufacturing Process of Vehicle Lithium‐Ion Battery Based on Correlation Coefficient and Multivariate Linear Regression Model

Abstract: Lithium-ion battery manufacturing is a multiprocess serial system and the consistency of each single cell will affect the performance and safety of battery system after grouping. Therefore, optimizing the battery preparation process and improving the battery consistency have become the key technical issues in battery preparation process. In this study, the inconsistency of finished batteries caused by manufacturing process is analyzed from three processes: electrode preparation, battery assembly, and liquid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The sample data of this study come from the previous publication, [ 6,7 ] in which the sample number is 49 565 soft‐pack batteries. Based on the process data, a BP prediction model is established to predict the consistency of capacity distribution, which can intervene and control the consistency problems before large‐scale manufacturing in time.…”
Section: Capacity Consistency Prediction Of Lithium‐ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample data of this study come from the previous publication, [ 6,7 ] in which the sample number is 49 565 soft‐pack batteries. Based on the process data, a BP prediction model is established to predict the consistency of capacity distribution, which can intervene and control the consistency problems before large‐scale manufacturing in time.…”
Section: Capacity Consistency Prediction Of Lithium‐ion Batteriesmentioning
confidence: 99%
“…[ 6 ] In addition, based on the collected 49 565 soft‐pack battery process data samples, Pearson correlation coefficient and multiple regression equation are carried out to quantify the correlation and contribution of process parameters to the consistency, which can be concluded that the influence weight of multiple process link data on battery grading capacity is high. [ 7 ] Therefore, the main purpose of this study is to enhance the capacity consistency through the prediction of battery capacity consistency and optimization of process parameters achieved by theoretical models to quantify the manufacturing process parameter formulation under the premise of optimal capacity consistency.…”
Section: Introductionmentioning
confidence: 99%
“…At present, according to the different research methods of battery cell inconsistency fault diagnosis, it can be roughly divided into statistical analysis methods, machine learning methods based on outlier detection, neural network algorithm, signal processing method based on information entropy analysis, and so forth. [20][21][22][23][24][25][26][27][28] Gasper et al 23 used machine learning-assisted model recognition methods to predict battery life, with uncertainty quantified by bootstrap resampling, and the uncertainty of life prediction is greatly reduced. Xia et al 7 established a model for short-term capacity estimation and long-term remaining useful life prediction of lithium-ion batteries based on data-driven methods.…”
Section: Introductionmentioning
confidence: 99%